2018
DOI: 10.15520/ijcrr.v9i11.624
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Work Motivation in Mediating the Effect Self Esteem and Self Efficacy on Employee Performance at CV. Alam Tanpaka, Denpasar Bali

Abstract: This study aims to analyze the role of work motivation in mediating the effect self esteem and self efficacy on employee performance at CV. Alam Tanpaka, Denpasar Bali. The study was conducted in 2018, with data collection techniques through interviews and questionnaires. The number of respondents is 52 employees. The analysis technique used is multiple linear regression with the SPSS Version 23 application for Windows and Sobel test. The results showed that self esteem, self efficacy had no effect on work mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…The results of this study are consistent with the results of research conducted by Angreni (2015), Widyawati et al (2018) states that self efficacy has a positive and significant effect on employee performance. Self efficacy is the confidence of every employee in facing and regretting the problems they face in various situations and being able to determine actions in completing certain tasks or problems.…”
Section: Discussion Of Hypothesissupporting
confidence: 92%
“…The results of this study are consistent with the results of research conducted by Angreni (2015), Widyawati et al (2018) states that self efficacy has a positive and significant effect on employee performance. Self efficacy is the confidence of every employee in facing and regretting the problems they face in various situations and being able to determine actions in completing certain tasks or problems.…”
Section: Discussion Of Hypothesissupporting
confidence: 92%
“…Whereas Lippke (2020) explain that self-efficacy is what an individual believes he or she can accomplish using his or her skills under certain circumstances. Widyawati, Sujana and Sukadana (2018) affirms that self-efficacy beliefs are judgments that individuals hold about their capabilities to learn or to perform courses of action at designated levels. Therefore, the basic principle behind self-efficacy theory is that individuals are more likely to engage in activities for which they have high self-efficacy and less likely to engage in those they do not.…”
Section: Self-efficacy Theorymentioning
confidence: 90%
“…Several researchers have conducted research related to service quality, customer satisfaction, company image and customer loyalty. The research results of Aryanto (2017), Pradhana (2015), Setyani (2014), Budiyanto (2013), Apriyadi (2017), found that service quality has a positive and significant effect on customer satisfaction. The opposite results are obtained from research Putranto (2016), Qomariah (2012), the quality of service has no effect on customer satisfaction.…”
Section: Supplementary Informationmentioning
confidence: 99%